International Evidence on Output Fluctuation and Shock Persistence - Daniel Levy; Hashem Dezhbakhsh (Bar-Ilan University, Department of Economics, 2002)
We estimate output growth rate spectra for 58 countries. The spectra exhibit diverse shapes. To study the sources of this diversity, we estimate the short-run, business cycle, and long-run frequency components of the sampled series. For most OECD countries the bulk of the spectral mass is in the business cycle frequency band, and the magnitude of this cyclical component increases with income. For the developing countries, however, the spectral mass is not concentrated in the business cycle frequency band, and the income-cycle relationship is not as strong. We also estimate two frequency domain measures of shock persistence and find both measures to vary considerably across countries, with the U.S. having the lowest estimates. For the OECD countries most of the variation in the variance ratio statistic appears to be explained by the variation in the long-term growth component.-
Keywords: C32; E30; E32; O40; O57; 330; Business Cycles; Developing Countries; OECD Countries; Output Growth; Shock Persistence; and Spectral Analysis